Penanaman Karakter Anak Usia Dini Melalui Pembelajaran Tari di Sanggar Arum Bandung - Nur Fadillah; Hartono Hartono (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study aims to describe and analzye the character building of early childhood through dance learning at Sanggar Arum Bandung. Dance learning is a form of non-formal education that plays an important role in developing character values in early childhood, such as discipline, responsibility, and cooperation. Early childhood is at a golden stage of development so it requires appropriate stimulation through fun and meaningful activities. The research method used is a qualitative method with a descriptive approach, namely collecting data through participatory observation, in-depth interviews, and documentation. These values are reflected in the discipline of children demonstrated through adherence to the practice schedule, the growth of self-confidence through the process of practice until performing in public, as well as the ability to work together in group movements and maintain cohesiveness. The results show that dance learning at Sanggar Arum Bandung is able to instill positive character values in children through the practice process, time discipline, and interaction between trainers and students. The conclusion of this study shows that dance learning is effective as a medium for character building in early childhood, so it can be an alternative learning that supports the development of children's personality and social skills.